Inovasi Pembelajaran PAI Berbasis Teknologi Informasi: Transformasi Digital dalam Pendidikan Islam - Adinda Zahrah; Amalia Setya Hanifah; Adiyas Adiyas; Abdul Azis (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This abstract discusses learning innovations in Islamic Religious Education (PAI) based on information technology as part of the digital transformation in Islamic education. This research aims to identify and analyze the application of information technology in the PAI learning process to improve the effectiveness, interactivity, and accessibility of Islamic education. A specific fact that is the focus is the rapid development of digital technology that influences traditional learning methods, as well as the urgent need to integrate technology into the PAI curriculum to suit the demands of the times. The research method uses a qualitative approach with case studies in several Islamic educational institutions that have implemented digital technology in PAI learning. The results of the research show that the use of information technology, such as digital learning applications, e-learning platforms and interactive multimedia, can increase student learning motivation, broaden the reach of education and support more personal and contextual learning. This research provides strategic recommendations for curriculum developers and educators to optimize the use of technology in PAI learning, while also emphasizing the importance of digital transformation as an effort to modernize sustainable Islamic education. Thus, PAI learning innovations based on information technology are key in facing the challenges and opportunities of the digital era.